Biosorption of Pb(II) from Aqueous Solution Using Cow Hooves: Kinetics and Thermodynamics. (6th June 2013) - Osasona, I.; Adebayo, A. O.; Ajayi, O. O.
Abstract : Biosorption of Pb(II) ions from aqueous solution by cow hooves (CHs) was investigated as a function of initial pH, contact time, and biosorbent dosage through batch studies. Equilibrium experiments were performed at three different temperatures (298, 308, and 318 K) using initial Pb 2+ concentration ranging from 15 to 100 mgg −1 . This study revealed that maximum uptake (96.2% removal) of Pb 2+ took place within 30 minutes of agitation, and the process was brought to equilibrium within 60 minutes of equilibration. The equilibrium data were modelled using Langmuir, Freundlich, and Dubinin-Radushkevich (D-R) isotherm models. The Langmuir isotherm model fitted the data best at all temperatures considered. The Lagergren second-order kinetic model fitted the biosorption process better than the first-order model. The negative values obtained for both Gibb's free energy change and enthalpy change are an indication of the spontaneous and exothermic nature of the sorption of Pb 2+ onto CH. A study of the FTIR spectral obtained before and after Pb 2+ sorption showed that carbonyl, hydroxyl, amino, and carboxyl groups were involved in the sorption process.